1999
DOI: 10.3354/meps178295
|View full text |Cite
|
Sign up to set email alerts
|

Influence of phylogeny, diet, moult schedule and sex on heavy metal concentrations in New Zealand Procellariiformes

Abstract: Mercury, cadmium, zinc and copper concentrations were analysed in the liver and ludney tissues of 14 species of albatross and petrel. These birds were obtained as by-catch of the long-line tuna fishing industry in New Zealand waters, and provided a unique opportunity to compare heavy metal accumulation in a group of closely related species. Mercury levels in the liver of the wandering and royal albatrosses were among the highest recorded for free-living birds. In multiple regression analyses, much of the inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
77
3

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(90 citation statements)
references
References 24 publications
10
77
3
Order By: Relevance
“…Metal levels obtained for adults in this study are generally comparable to those reported for petrels and shearwaters studied in other oceanic islands (Muirhead and Furness 1988, Stewart et al 1994, Stewart et al 1997a, Stewart et al 1999. Nevertheless, Se and Zn values observed in these birds were fairly high.…”
Section: Comparison With Other Species and Locationssupporting
confidence: 71%
See 2 more Smart Citations
“…Metal levels obtained for adults in this study are generally comparable to those reported for petrels and shearwaters studied in other oceanic islands (Muirhead and Furness 1988, Stewart et al 1994, Stewart et al 1997a, Stewart et al 1999. Nevertheless, Se and Zn values observed in these birds were fairly high.…”
Section: Comparison With Other Species and Locationssupporting
confidence: 71%
“…Only in the tropicbirds did juveniles have higher essential metal levels than adults. This same pattern has already been observed in various species (Kim et al 1998, Stewart et al 1999 in which the young accumulate essential elements to meet particularly high nutritional needs (Thompson et al 1996). This strategy may have evolved in order to survive the fast caused by the abandon of the fledglings by their parents several days before their first flight.…”
Section: Influence Of Phylogenysupporting
confidence: 50%
See 1 more Smart Citation
“…The increase in adult ivory gulls' MeHg was similar to mesopelagic-feeding seabirds from the Azores, (Calonectris diomedea: þ1.4% per year), but less than mesopelagic specialists (Bulweira bulwerii: þ2.9% per year, Oceanodroma castro: þ4.1% per year) [68]. Procellariiformes (albatrosses, shearwaters, petrels and storm-petrels), however, tend to have higher feather Hg concentrations than other species owing to their protracted moulting periods [69,70].…”
Section: Discussionmentioning
confidence: 97%
“…As such, their study can be highly informative about responses of birds to environmental constraints. In addition, results from the chemical analysis of feathers (mostly studies of stable isotopes, trace elements and pollutants) are used increasingly to infer trends in the spatial and trophic ecology of many species, as well as to determine levels of environmental contamination (Stewart et al 1999;Hobson and Wassenaar 2008;Inger and Bearhop 2008). In such studies, obtaining reliable information on timing of moult of different feather types is not only critical for validating results, but may also allow further inferences about variation among individuals, for example in migration strategies (González-Solís et al 2011).…”
Section: Introductionmentioning
confidence: 99%